2004
DOI: 10.1111/j.1467-9450.2004.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation strategies, coping process and acculturative stress

Abstract: Using structural equation modeling, this study examines the influences of motivational factors (Need for Cognitive Closure--NCC--and Decisiveness), coping strategies and acculturation strategies on levels of acculturative stress. Two groups of immigrants in Rome (Croatians n= 156 and Poles n= 179) completed a questionnaire that included scales for the various factors. Although our initial hypothesized model was not confirmed, a modified model showed that the motivational factors of NCC and Decisiveness indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 61 publications
(65 reference statements)
5
40
1
7
Order By: Relevance
“…In one study, immigrants with higher need for closure reported using avoidance coping strategies in adjusting to the new culture, which was also linked to reduced contact with host nationals (Kosic, 2004). Other studies suggest that need for closure is particularly important for personal and interaction adjustment.…”
Section: Need For Closurementioning
confidence: 99%
“…In one study, immigrants with higher need for closure reported using avoidance coping strategies in adjusting to the new culture, which was also linked to reduced contact with host nationals (Kosic, 2004). Other studies suggest that need for closure is particularly important for personal and interaction adjustment.…”
Section: Need For Closurementioning
confidence: 99%
“…A few studies suggest that the sociopolitical context (Bourhis, Moïse, Perreault, & Senécal, 1997;Bourhis, Montaruli, El-Geledi, Harvey, & Barrette, 2010), demographic characteristics (Allen, Vaage, & Hauff, 2006), and personality factors such as need for cognitive closure (Kosic, 2004(Kosic, , 2006 influence cultural orientations. Longitudinal studies starting ideally right before migration or very shortly after would allow for the identification of initial predictors of acculturation trajectories, which, in turn, would facilitate the identification of individuals who are more likely to experience psychosocial adjustment difficulties (Nguyen and BenetMartínez, 2013).…”
Section: Acculturation Orientations: Temporal Dynamics and Antecedentsmentioning
confidence: 99%
“…The three most frequently mentioned coping strategies include task-oriented strategies, emotion-oriented strategies, and avoidance-oriented strategies (Carver, Scheier, & Weintraub, 1989;Endler & Parker, 1990, 1994Kosic, 2004). Task-oriented coping strategies reduce stress by focusing on immediate problems.…”
Section: Stress-coping Strategymentioning
confidence: 99%